PENGARUH PEMENUHAN KEBUTUHAN ANAK DIDIK TERHADAP PROSES AKTUALISASI DIRI ANAK PADA PENDIDIKAN ANAK USIA DINI (PAUD) SANTO VINCENTIUS A PAULO KUPANG - Lestari, Anastasia Yani; Dau, Yoseph Lodowik Deki; Januru, La (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2021)
This study aims to examine whether the need of students can affect the process of self-actualization of children at Paud Santo Vincentius A Paulo Kupang. In this study, an analysis was carried out on each indicator of the variable need of students and the variable of the child's self-actualization process so that it can be seen whether there is an influence relationship between the two variables. The population of this study consisted of 66 people: PAUD managers, teachers, and parents. The research sample was taken using the saturated sample technique. The result of the descriptive statistical analysis showed that the student's need was categorized as good with a score of 73.32%, and the self-actualization process was also in a good category with a score of 69.71%. The result of the partial effect test shows that there is a positive and significant influence between student's needs on the process of self-actualization of children at Paud Santo Vincentius A Paulo Kupang (t test value 4.176 and sig. 0.000 <0.05). It is recommended that PAUD managers need to complete learning facilities, create an environment that supports the development of children's potential, educators need to provide guidance, assistance, and direction that motivates children to develop aspects that help actualization, parents need to be actively involved in activities that encourage self-actualization that programmed by the school in order to help children develop their potential as optimally as possible.